How they choked : failures, flops, and flaws of the awfully famous - Bragg, Georgia (Walker Books for Young Readers, an imprint of Bloomsbury, 2014)
Presents a humorous look at the flaws and foibles of some of the most famous personalities of history, including such figures as Marco Polo, George Armstrong Custer, Thomas Edison, and Amelia Earhart.